2000
DOI: 10.1086/315713
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Tumor Necrosis Factor–α and Interleukin‐1β in Bacterial Vaginosis May Increase Susceptibility to Human Immunodeficiency Virus

Abstract: Bacterial vaginosis (BV) was identified recently as a cofactor that promotes sexual transmission of human immunodeficiency virus (HIV). This study was done to determine if interleukin (IL)-1beta and tumor necrosis factor (TNF)-alpha could be measured consistently in cervical secretions and if high levels of these cytokines were associated with BV. Secretions were obtained from 209 study subjects; most samples had detectable levels of TNF-alpha (84.2%) and IL-1beta (79.8%). BV was detected in 53 (27.0%) of 196 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
86
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(93 citation statements)
references
References 42 publications
5
86
0
2
Order By: Relevance
“…Lactobacillus iners was prominent in all patients posttreatment. Atopobium vaginae concentrations were highest for patients who failed or responded incompletely to treatment and lowest for patients who were cured.Bacterial vaginosis (BV) is the most common cause of vaginal irritation and is associated with adverse pregnancy outcomes (4, 13) and an increased risk of human immunodeficiency virus infection (14,15). BV results when the normal, predominantly Lactobacillus vaginal flora shifts to one dominated by Gardnerella vaginalis, Mycoplasma hominis, and a variety of anaerobic organisms.…”
mentioning
confidence: 99%
“…Lactobacillus iners was prominent in all patients posttreatment. Atopobium vaginae concentrations were highest for patients who failed or responded incompletely to treatment and lowest for patients who were cured.Bacterial vaginosis (BV) is the most common cause of vaginal irritation and is associated with adverse pregnancy outcomes (4, 13) and an increased risk of human immunodeficiency virus infection (14,15). BV results when the normal, predominantly Lactobacillus vaginal flora shifts to one dominated by Gardnerella vaginalis, Mycoplasma hominis, and a variety of anaerobic organisms.…”
mentioning
confidence: 99%
“…Increased vaginal concentrations of IL-1␤ have been consistently found in women with BV, and HIV. [27][28][29][30] In vaginal fluid, IL-1␤ was positively associated with IL-8 (CXCL8) a potent chemokine. 29 Both of these proinflammatory cytokines were consistently correlated with the number of vaginal neutrophils, in healthy and BV-positive women.…”
mentioning
confidence: 99%
“…29 Both of these proinflammatory cytokines were consistently correlated with the number of vaginal neutrophils, in healthy and BV-positive women. 4,27,29 Though a number of studies have examined vaginal immunity in BV positive women, few investigations have examined the modulation of vaginal immunity by T vaginalis in BVpositive women. A study showed that vaginal discharges of symptomatic trichomoniasis patients had large amounts of IL-8.…”
mentioning
confidence: 99%
“…Accumulating evidence suggests that microbes associated with BV modulate the immune response [27,31,[33][34][35][36]. Many authors have found elevate levels of interleukin (IL)-1alpha or beta in vaginal secretions of BV-positive women compared to healthy controls [34,[37][38][39][40]. IL-1beta is a member of the IL-1 family, which includes the classical IL-1alpha (IL-1F1) and IL-1beta (IL-1F2) cytokines, IL-1 receptor antagonist (IL-1ra, or IL-1F3), IL-18 (IL-1F4), and the newly described IL-1F5-11 [41].…”
Section: Introductionmentioning
confidence: 99%